Changes in paraspinal muscles and facet joints after percutaneous endoscopic transforaminal lumbar interbody fusion for the treatment of lumbar spinal stenosis: A 3-year follow-up - Pang, Daming; Yang, Jincai; Hai, Yong; Fan, Zhexuan; Gao, Haifeng; Yin, Peng (Frontiers in Surgery, 2022)
Objectives: This study investigates the changes in the paraspinal muscles of lumbar spinal stenosis patients after percutaneous endoscopic transforaminal lumbar interbody fusion (PE-TLIF). Methods: Thirty-three patients from Beijing Chaoyang Hospital who had L4/5 segment lumbar spinal stenosis between January, 2017 and January, 2019were included in this study. Patient-reported outcomes including the visual analog scale scores for back pain and leg pain (VAS-BP and VAS-LP, respectively) and the Oswestry disability index (ODI) scores at pre-operation and 1-week, 3-month, 12-month, and (at least) 3-year follow-up (the final follow-up) were evaluated. Computed tomography (CT) was performed at the 12-month follow-up, 24-month follow-up, and the final follow-up after surgery. Multifidus (MF) muscle functional cross-sectional area (FCSA) and fat infiltration (FI) were evaluated, and the degree of adjacent facet joint degeneration was evaluated using Pathria scores. Results: All patients underwent at least a 3-year follow-up period. The VAS-BP, VAS-LP, and ODI were significantly lower at 1-week, 3-month, 12-month, and 3-year follow-up than at pre-operation (P<0.05). At the 3-year follow-up, no differences were found in FCSA and FI for any patient’s MF muscle at the lower third of the vertebral body (L3) above the operation level (P>0.05), and there was no statistical difference in the central plane of the L3/4 and L5/S1 vertebral facet joints at pre-operation, 12-month, 24-month, and 3-month follow-up (P>0.05). Conclusions: PE-TLIF can provide satisfactory clinical outcomes for patients with lumbar spinal stenosis. Furthermore, the technique may also reduce the injury on the paravertebral muscles, especially the MF muscle, as well as on adjacent facet joints.